Comparing post-soviet and Latin American societies: from “transition” to “transformation" - Heredia, Mariana Laura (2010)
Introduction to a thematic issue entitled “Russia/former USSR/Latin America: Studies in Post-Authoritarian Transformation.” Because of language barriers and a lack of institutionalized ties, the impressive literature on democratization in each of these areas is virtually unknown to authors from the other region. The striking similarities between the former Soviet Union and Latin America are best studied through comparison based on ground-level fieldwork. This approach highlights the blind spots of standard democratization and free-market modernization theory, which tends to universalize scenarios of economic development without paying sufficient attention to case studies. The introduction outlines the conceptual shift from “transition” to “transformation” in the literature on democratization, and presents the articles in the issue as well as some of the challenges the editors faced in bringing authors from Latin America and the former USSR together. English and Russian versions.